2020
DOI: 10.2147/cia.s283809
|View full text |Cite
|
Sign up to set email alerts
|

<p>Application of Titanium Alloy 3D-Printed Artificial Vertebral Body for Stage III Kümmell’s Disease Complicated by Neurological Deficits</p>

Abstract: The current study aimed to compare the clinical and radiographic results of the 3D-printed artificial vertebral body (3DP-AVB) and titanium mesh cage (TMC) for the treatment of Kümmell's disease (KD) complicated by neurological deficits. Patients and Methods: From January 2014 to July 2018, 28 consecutive patients diagnosed with KD and nerve injuries in our department were treated by posterior vertebral column resection and internal fixation. The patients were divided into two groups (3DP-AVB group and TMC gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The 3D-printed AVB was designed according to the location of the tumor and physiological curvature of the spine. The large contact area is conducive to the adhesion of bone tissue cells and provides good stability ( 37 ). Its three-dimensional microporous structure renders it high in strength and low in modulus, and it is less prone to the stress shielding effect.…”
Section: Discussionmentioning
confidence: 99%
“…The 3D-printed AVB was designed according to the location of the tumor and physiological curvature of the spine. The large contact area is conducive to the adhesion of bone tissue cells and provides good stability ( 37 ). Its three-dimensional microporous structure renders it high in strength and low in modulus, and it is less prone to the stress shielding effect.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, more and more studies have reported the application of customized 3D‐printed titanium alloy pore metal artificial vertebra, which gave us more options for cervical stability reconstruction 22–24 . Based on our experience, we designed a spacer for the concave facet joint and the anterior intervertebral space during preoperative planning.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, more and more studies have reported the application of customized 3D‐printed titanium alloy pore metal artificial vertebra, which gave us more options for cervical stability reconstruction. 22 , 23 , 24 Based on our experience, we designed a spacer for the concave facet joint and the anterior intervertebral space during preoperative planning. The rough surface of the spacer provided immediate stability and effectively reduced the stress borne by the screw, reducing the possibility of internal fixation failure.…”
Section: Discussionmentioning
confidence: 99%
“…Current spinal cages for interbody fusion procedures may lead to endplate fractures and collapse. Due to the particular usefulness of 3D printing in reconstructing complex geometries, they can be used in areas where current implants are not suitable to replace local anatomical structures [ 233 ]. In anterior cervical discectomy fusion (ACDF), 3D printing cages could significantly relieve symptoms, restore the curvature of the cervical spine, effectively maintain the intervertebral height for a long time, and prevent complications related to postoperative subsidence [ 234 ].…”
Section: Clinical Applicationsmentioning
confidence: 99%